FAKTOR-FAKTOR YANG BERPERAN MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN TERHADAP PRODUK SUSU SEGAR DAN OLAHAN DI MALANG: Studi Kasus di Koperasi SAE Pujon - Ariani Trisna Murti; Karunia Setyowati; Farida Kusuma Astuti (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2022)
The research was conducted using a survey method at the KOP SAE, Pujon, Malang in March 2020 with the consideration that the SAE Dairy Cooperative in Pujon is one of the largest dairy cooperatives in Malang which supplies a lot of milk to several dairy processing industries. The data used are primary and secondary data, where primary data is obtained from the results of questionnaires filled in by respondents from research sites, journals, and books to support research results. The number of samples selected was 100 people using the purposive sampling method. The data analysis method used the descriptive qualitative analysis method by obtaining the correlation between marketing mix variables (product, price, place, promotion, and people) on consumer purchasing decisions in buying fresh milk products and processed products at the KOP SAE, Pujon, Malang Regency. The conclusion of the research is that product variable, place variables, and promotion variables have a dominant influence on consumer purchasing decisions in buying fresh and processed milk products with significance values of 0.285, 0.256, and 0.223 respectively. While the service and price variables simultaneously provide a positive relationship and correlation with sequential values of 0.211 and 0.164, therefore it is considered less significant in influencing consumer decisions in buying fresh and processed milk products in the KOP SAE, Pujon, Malang.